Protein S protects against allergic bronchial asthma by modulating Th1/Th2 balance. Issue 9 (23rd March 2020) - Asayama, Kentaro; Kobayashi, Tetsu; D'Alessandro‐Gabazza, Corina N.; Toda, Masaaki; Yasuma, Taro; Fujimoto, Hajime; Okano, Tomohito; Saiki, Haruko; Takeshita, Atsuro; Fujiwara, Kentaro; Fridman D'Alessandro, Valeria; Nishihama, Kota; et al.
Abstract: Background: Bronchial asthma is a chronic disease characterized by inflammation, obstruction, and hyperresponsiveness of the airways. There is currently no curative therapy for asthma. Type 2 helper T cell response plays a critical role in the pathogenesis of the disease. Protein S is a glycoprotein endowed with anticoagulant, anti‐inflammatory, and anti‐apoptotic properties. Whether protein S can suppress bronchial asthma and be useful for its therapy is unknown. Methods: To address this question here we compared the development of allergen‐associated bronchial asthma between wild type and protein S‐overexpressing transgenic mice. Mice were sensitized and challenged with ovalbumin. We also evaluated the circulating levels of total and active protein S in patients with bronchial asthma and healthy controls. Results: The circulating level of total protein S and of its active form was significantly decreased in patients with bronchial asthma compared to controls. Allergic protein S transgenic mice showed a significant reduction of airway hyperresponsiveness, lung tissue inflammatory cell infiltration, lung levels of Th2 cytokines and IgE compared to their wild‐type counterparts. Administration of exogenous human protein S also decreased airway hyperresponsiveness and Th2‐mediated lung inflammation in allergic wild‐type mice compared with their untreated mouse counterparts. Human protein S significantly shifted the Th1/Th2 balance to Th1 and promoted the secretion of Th1 cytokines (IL‐12, tumor necrosis factor‐α) from dendritic cells. Conclusions: These observations suggest the strong protective activity of protein S against the development of allergic bronchial asthma implicating its potential usefulness for the disease treatment. Abstract : Patients with allergic bronchial asthma have reduced circulating level of active PS. Administration of exogenous PS attenuates allergic airway inflammation and hyperresponsiveness in mice. In the presence of protein S, allergen presentation by dendritic cells to T‐cells shifts the Th1/Th2 immune balance towards Th1 and inhibits allergic response in the airways; therefore, PS has the potential to become a drug for the treatment of allergic bronchial asthma. Abbreviations: OVA, ovalbumin; PS, protein S